2020
DOI: 10.3390/jcm9092702
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Clearance by Direct-Acting Antivirals Impacts Glucose and Lipid Homeostasis

Abstract: Background: Chronic hepatitis C virus (HCV) infections are causally linked with metabolic comorbidities such as insulin resistance, hepatic steatosis, and dyslipidemia. However, the clinical impact of HCV eradication achieved by direct-acting antivirals (DAAs) on glucose and lipid homeostasis is still controversial. The study aimed to prospectively investigate whether antiviral therapy of HCV with DAAs alters glucose and lipid parameters. Methods: 50 patients with chronic HCV who were treated with DAAs were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
0
32
1
1
Order By: Relevance
“…Our results were also in agreement with (Townsend et al, 2015) who described marked increase in serum low-density lipoprotein cholesterol (LDL-C) in HCV monoinfected or HCV/HIV coinfected patients treated with sofosbuvir and ribavirin (SOF/RBV) or ledipasvir/sofosbuvir combination therapy and report that the increase in serum LDL-C during HCV therapy was independent of the type of HCV therapy, and was likely reflective of the host's response to HCV suppression. In Addition to (EL-Lehleh et al, 2019) [32] who concluded that Successful eradication of HCV was associated with an increase in the serum level of TC, TGs, LDL-C, and HDL-C irrespective of the therapy protocol (DCV + SOF ± RBV), While (Graf et al, 2020) [33] observed a significant increase in total cholesterol, HDL, and LDL during and after antiviral therapy. Moreover, their results show a dynamic change of serum lipid parameters with a significant increase in lipid parameters and CAP (a measure of liver steatosis) values from baseline to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Our results were also in agreement with (Townsend et al, 2015) who described marked increase in serum low-density lipoprotein cholesterol (LDL-C) in HCV monoinfected or HCV/HIV coinfected patients treated with sofosbuvir and ribavirin (SOF/RBV) or ledipasvir/sofosbuvir combination therapy and report that the increase in serum LDL-C during HCV therapy was independent of the type of HCV therapy, and was likely reflective of the host's response to HCV suppression. In Addition to (EL-Lehleh et al, 2019) [32] who concluded that Successful eradication of HCV was associated with an increase in the serum level of TC, TGs, LDL-C, and HDL-C irrespective of the therapy protocol (DCV + SOF ± RBV), While (Graf et al, 2020) [33] observed a significant increase in total cholesterol, HDL, and LDL during and after antiviral therapy. Moreover, their results show a dynamic change of serum lipid parameters with a significant increase in lipid parameters and CAP (a measure of liver steatosis) values from baseline to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported recovery from HCV-induced hypolipidaemia after DAA treatment [ 66 , 67 , 68 , 69 , 70 ]. However, most studies showed that ANGPTL-targeted lipid species, such as triglycerides and VLDL cholesterol, remained the same before and after DAA treatment, even at 24-week follow-ups [ 66 , 67 , 68 , 71 ]. Alternatively, a moderate post-cure increase was noted only in patients with mild fibrosis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hastalık ne kadar erken yakalanırsa enfekte kişilerin fayda görme oranı da o kadar artmaktadır (9). DOA ile HCV eradikasyonunun sadece hepatik komplikasyonları azaltmadığı, kardiyovasküler hastalık riskini azalttığı, glisemik kontrol üzerinde etkili olduğuna dair çalışmalar da yayınlanmaktadır (11,12) taların da içinde olduğu toplam 18 hasta tedavi alabilmiş, hepsi SVR 12'ye ulaşmıştır. Bu hastaların kronik karaciğer hastalığının komplikasyonlarından korunabilecek olması önemlidir.…”
Section: Discussionunclassified